Construction of Hsp90-based fluorescent molecular probe and evaluation of pancreatic tumor recognition effects - LUO Haojun, KONG Dexin, HUANG Wei, YANG Nan, LIU Yanyong (Jichu yixue yu linchuang)
Objective To construct fluorescent molecular probes targeting at tumor heat shock protein 90 (Hsp90) in order to enhance tumor-specific recognition. Methods The human pancreatic adenocarcinoma cell line PANC-1 and the human small cell lung cancer cell line NCI-H446 were used as the research targets to study the uptake and clearance of Cy5-P7 by tumor cells with flow cytometry as well as immune-fluorescence technology; The mechanism to mediate entrance of Cy5-P7 into the cells by Hsp90 was investigated by blocking of the PANC-1 cell surface proteins with monoclonal antibody to Hsp90; Human pancreatic cancer cell line PANC-1 was subcutaneously injected into posterior dorsum of BALB/c nude mice to construct a xenogeneic subcutaneous tumor model to validate the in vivo tumor recognition ability by Cy7-P7 as well as its in vivo distribution in mice. Results The uptake of Cy5-P7 by cells was significantly reduced in low temperature (P＜0.05); An average fluorescence intensity in Cy5-P7-treated cells was significantly reduced after blocking with a monoclonal antibody to Hsp90(P＜0.05); The fluorescence intensity at the tumor site of Cy7-P7 group was higher than that of control group (P＜0.05), and there was a significant presence of Cy7-P7 in the kidney and tumor fluorescence. Conclusions Cy5-P7 can effectively target at Hsp90, and its specific binding significantly enhanced the cellular uptake of Cy5-P7 fluorescent probe, which improved the sensitivity and accuracy of fluorescence imaging. Cy7-P7 showed good tumor active recognition in vivo, and was able to be enriched at the tumor site and metabolized out of the body in 48 h, which may effectively support accurate tumor recognition.